Atrophy, ultra-structural disorders, severe atrophy and degeneration of denervated human muscle in SCI and Aging. Implications for their recovery by Functional Electrical Stimulation, updated 2017. (3rd July 2017) - Kern, Helmut; Hofer, Cristian; Loefler, Stefan; Zampieri, Sandra; Gargiulo, Paolo; Baba, Alfonc; Marcante, Andrea; Piccione, Francesco; Pond, Amber; Carraro, Ugo
Abstract: Objectives: Long-term lower motor neuron denervation of skeletal muscle is known to result in degeneration of muscle with replacement by adipose and fibrotic tissues. However, long-term survival of a subset of skeletal myofibers also occurs. Methods: We performed transverse and longitudinal studies of patients with spinal cord injury (SCI), patients specifically complete Conus and Cauda Equina Syndrome and also of active and sedentary seniors which included analyses of muscle biopsies from the quadriceps m . Results: Surprisingly, we discovered that human denervated myofibers survive years of denervation after full and irreversible disconnection from their motor neurons. We found that atrophic myofibers could be rescued by home-based Functional Electrical Stimulation (h-bFES), using purpose developed stimulators and electrodes. Although denervated myofibers quickly lose the ability to sustain high-frequency contractions, they respond to very long impulses that are able to allow for re-emergence of tetanic contractions. A description of the early muscle changes in humans are hampered by a paucity of patients suffering complete Conus and Cauda Equina Syndrome, but the cohort enrolled in the EU RISE Project has shown that even five years after SCI, severe atrophic myofibers with a peculiar cluster reorganization of myonuclei are present in human muscles and respond to h-bFES. Conclusions: Human myofibers survive permanent denervation longer than generally accepted and they respond to h-bFES beyond the stage of simple atrophy. Furthermore, long-term denervation/reinnervation events occur in elderly people and are part of the mechanisms responsible for muscle aging and again h-bFES was beneficial in delaying aging decay.